»3 hat kûllar fûlla soûda«: Ur Mäster Gustaf Johan Jungs anteckningsbok i Uppsala universitetsbibliotek – En kort översikt - Henricson, Lars G. (Hikuin, 2010)
»3 hat bulbs full with soda« From the notebook by Gustaf Johan Jung in Uppsala university libraries – a brief overview By Lars G. Henricson A very important document, written by Gustaf Johan Jung, concerning the study of Swedish but also other European glass industries, during the second part of the 1700th century, is kept in Uppsala university library. Gustaf Johan Jung was the son of Melchior Jung, a significant entrepreneur in the glass industry during the Swedish great power era. Gustaf Jung’s notebook contains notes, different observations and drawings from total 27 years’ experiences (1666-1693) of the glass handicrafts and industry, and from at least 6 years’ study travels to different European countries, England, France and perhaps also Germany, Holland, Italy and Denmark. Jung’s original manuscripts, to the overwhelming part written in Swedish, but even in English and French, has now been interpreted and translated to understandable Swedish text. His work will contribute with important supplementary completions to a broader European research. In this short essay, some notes and illustrations from Gustaf Jung´s notebook will be discussed.